Penggunaan Botes AHW sebagai Alat Siram Tetes dalam Pembudidayaan Cendana di Kabupaten Belu, NTT - Albert Husein Wawo; Rochadi Abdulhadi (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
One of factors that causes the failure of the sandalwood cultivation in East Nusa Tenggara Province is drought of seedlings after planting. This research has been conducted to study the use of Botes-AHW as an equipment of drip watering on sandalwood cultivation and to evaluate the water requirements in seedling growth after planting. The results showed that the use of water was more conserved by employing the Botes-AHW in sandalwood cultivation than the traditional watering system. The average of water requirements in seedling growth (several months after planting) is 10 liters per seedling per month.